Benzohydroxamic acid on rutile TiO2(110)-(1×1)– a comparison of ultrahigh-vacuum evaporation with deposition from solution - Köbl, Julia; Fernández, Cynthia C.; Augustin, Lisa-Marie; Kataev, Elmar; Franchi, Stefano; Tsud, Nataliya; Pistonesi, Carolina; Pronsato, M. Estela; Jux, Norbert; Lytken, Ole; Williams, Federico J.; Steinrück, Hans-Peter (Surface Science, 2022)
Hydroxamic acids are an interesting anchor group for organic molecules on oxide surfaces, but very few studies exist on their adsorption on well-defined single-crystal surfaces under well-defined conditions. In the present paper, we use X-ray photoelectron spectroscopy to follow the adsorption of benzohydroxamic acid on a rutile TiO2(110)-(1×1) single-crystal surface. We compare evaporation in ultrahigh vacuum with deposition from ethanol and acetonitrile solutions. Furthermore, we carried out density functional theory calculations to support the assignment of adsorbates. Several species appear on the surface, which are most evident in the N 1s region. The low-coverage species can be explained as originating from a hydroxamate, and decomposed species related to oxygen vacancies or defects. Identification of the high-coverage species, however, remains elusive, and several possibilities are discussed.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Benzohydroxamic acid; Density functional theory calculations; TiO; X-ray photoelectron spectroscopy (XPS)

Wet-chemically prepared porphyrin layers on rutile tio2(110) - Wechsler, Daniel; Carolina Fernandez, Cynthia; Köbl, Julia; Augustin, Lisa-Marie; Stumm, Corinna; Jux, Norbert; Steinrück, Hans-Peter; Williams, Federico Jose; Lytken, Ole (Molecules, 2021)
Porphyrins are large organic molecules that are interesting for different applications, such as photovoltaic cells, gas sensors, or in catalysis. For many of these applications, the interactions between adsorbed molecules and surfaces play a crucial role. Studies of porphyrins on surfaces typically fall into one of two groups: (1) evaporation onto well-defined single-crystal surfaces under well-controlled ultrahigh vacuum conditions or (2) more application-oriented wet chemical deposition onto less well-defined high surface area surfaces under ambient conditions. In this study, we will investigate the wet chemical deposition of 5-(monocarboxyphenyl)-10,15,20-triphenylporphyrin (MCTPP) on well-defined rutile TiO2 (110) single crystals under ambient conditions. Prior to deposition, the TiO2(110) crystals were also cleaned wet-chemically under ambient conditions, meaning none of the preparation steps were done in ultrahigh vacuum. However, after each preparation step, the surfaces were characterized in ultrahigh vacuum with X-ray photoelectron spectroscopy (XPS) and the result was compared with porphyrin layers prepared in ultrahigh vacuum (UHV) by evaporation. The differences of both preparations when exposed to zinc ion solutions will also be discussed.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Interfaces; Metalation; Oxide surfaces; Porphyrins; Wet chemical preparation